Modulated luminescence of zero-dimensional bimetallic all-inorganic halide clusters. Issue 15 (24th June 2022) - Zhang, Chao; Feng, Xuezhen; Song, Qilin; Zhou, Chaocheng; Peng, Lin; Liu, Xiaolin; Chen, Hong; Lin, Jia
Abstract : A series of new zero-dimensional bimetallic all-inorganic halide clusters were reported, and the luminescence of the clusters was regulated by both the B(i ) connecting ions and B(iii ) ions in the octahedral centers. Abstract : Zero-dimensional (0D) metal halide clusters formed as isolated metal halide polyhedral structures show excellent optical properties and have great potential for various applications in optoelectronic devices. In this study, we reported a series of Rb8 CuB(iii )3 Cl18 single crystals (SCs) constructed from Cu(i ) and B(iii ) (B = In, Tb, etc .) containing lead-free bimetallic halide clusters. Density functional theory calculations have been used to explore the thermodynamic stability of the expected bimetallic halide clusters, in which the ionic radius of B(iii ) trivalent metal cations should be within the range of 0.74 to 0.99 Å in order to form a stable Rb8 CuB(iii )3 Cl18 0D structure in line with the same structure configuration. By analyzing the effects of different B(iii ) cations on the structural parameters and optical-physical properties, we found that the luminescence of SCs could be modulated by different B(iii ) cations, while the luminescence originated from the charge transfer from Cu(i ) ions to metal-chloride octahedra. This study reported the rational design of novel-structured Cu(i )-based inorganic lead-free metal halide materials, which paves the way for the exploration of new luminescent materials.